Application of Electromagnetic Induction Technique to Measure the Void Fraction in Oil/Gas Two Phase Flow - Abdul Wahhab, H.A. (Institute of Physics Publishing, 2018)
In this work, electromagnetic induction technique of measuring void fraction in liquid/gas fuel flow was utilized. In order to improve the electric properties of liquid fuel, an iron oxide Fe3O4 nanoparticles at 3 was blended to enhance the liquid fuel magnetization. Experiments have been conducted for a wide range of liquid and gas superficial velocities. From the experimental results, it was realized that there is an existing linear relationship between the void fraction and the measured electromotive force, when induction coils were connected in series for excitation coils, regardless of increase or decrease CNG bubbles distribution in liquid fuel flow. Therefore, it was revealed that the utilized method yielded quite reasonable account for measuring the void fraction, showing good agreement with the other available measurement techniques in the two-phase flow, and also with the published literature of the bubbly flow pattern. From the results of the present investigation, it has been proven that the electromagnetic induction is a feasible technique for the actual measurement of void fraction in a Diesel/CNG fuel flow. Â© Published under licence by IOP Publishing Ltd.